Prosedur dan Syarat Poligami di Indonesia dan Malaysia - Siti Nor Aishah; Siti Zailia; Armasito Armasito (Muqaranah, 2022)
Abstract: This research aims to examine the requirements for polygamy in Indonesia and Malaysia. As it is known that Indonesia and Malaysia can be said to be Islamic countries. The author uses a normative legal research method with a comparative approach. It is said to be normative legal research because this paper examines statutory regulations. A comparative approach is used because this study intends to examine the comparison between the rules of polygamy in Indonesia and Malaysia. The results of the study show that there are similarities between Indonesia and Malaysia regarding polygamy, namely that both must obtain a permit issued by the court. The difference lies in the permission of the first wife. The conditions for polygamy in Indonesia must have permission from the first wife, while in Malaysia there is no need for permission from the first wife, but it is sufficient at the discretion of the judge. Thus, it can be concluded that marriages with more than one wife, both in Indonesia and Malaysia, are considered legal and legally recognized by the state if the marriage obtains permission from the court.